Writing-reading devices: intermediations. - Marques da Silva, Ana; Bettencourt, Sandra (Neohelicon, 2017)
Exploring the widening of literary practices, and demystifying boundaries in genres, sensory modalities, reading/writing processes and devices, this paper analyses two types of crossovers and intermediations: distributed authorship in the writing of digital generative literature, and the feedback loops between the screen and the book in contemporary experimental works. Nick Montfort and Marc Saporta's works are analysed as enactive systems that emerge from the intersections between different modes of production and perception, highlighting the ways in which writing and reading strategies are reconfigured in contemporary experiences with literary forms and theoretical frameworks.